Achieving halogen bonding enhanced ultra-highly efficient AIE and reversible mechanochromism properties of TPE-based luminogens: position of bromine substituents. Issue 21 (18th May 2022) - Miao, Xinrui; Cai, Zhengkai; Zou, Hengqi; Li, Jinxing; Zhang, Songyao; Ying, Lei; Deng, Wenli
Abstract : Crystal of o -BrTBE and self-assembled balls of m -BrTBE film show ultra-highly efficient AIE and reversible mechanochromism (MC) properties as obvious anti-heavy atom effects resulting from the formation of intermolecular Br⋯Br bonds. Abstract : Intelligent aggregation-induced emission (AIE) materials based on organic photoresponsive mechanochromism (MC) with high luminous efficiency have received much attention for their wide application in luminescent devices. However, halogen substituents have rarely been adopted to tune MC and enhance the AIE properties. Herein, phenyl and different positions of bromine substituents were systematically introduced into the tetraphenylethylene (TPE) unit, including TBE, o -BrTBE, m -BrTBE, and p -BrTBE, to deeply explore the halogen bonding enhanced AIE and MC properties. TBE, o -BrTBE, and p -BrTBE crystals with stronger intralayer and interlayer interactions had higher fluorescence quantum yield ( Φ F ) values than those of films. Interestingly, m -BrTBE had a lower Φ F value in the crystalline state than the film, which was ascribed to the formation of stronger Br⋯Br bonds in the amorphous state. o -BrTBE had the highest Φ F value (93%) in the crystalline state and m -BrTBE forming ball-like aggregations had the highest Φ F value (98%) in the film. In the crystalline state, the strength of C–H⋯π, C–Br⋯π, and Br⋯Br bonds determines the photoluminescence intensity. Careful analysis of their optical properties and crystal structures combined with theoretical calculations confirmed that different positions of bromine substituents can lead to the formation of diverse intermolecular interactions, in which the intermolecular Br⋯Br bonds play the dominant role in the ultra-highly efficient fluorescence. The ground powders had higher Φ F values than the as-prepared solid powders. The power X-ray diffraction (PXRD) and field-emission scanning electron microscopy (FESEM) results indicated that the TBE derivatives fabricated by grinding and displaying good MC performance and distinguishable emission change could contribute to the crystalline to amorphous phase or different crystal phases transition. Our work reports the highest luminous efficiency based on the anti-heavy atom effect on AIE materials reported so far, which is helpful to further explore their applications, such as in anti-counterfeiting inks for banknotes.